Impact of built environment on thermal perceptions among office workers in tropical low carbon city: a physical inactivity awareness assessment - Dahlan, Nur Dalilah; Kurmanbekova, Mainur; Shari, Zalina; Abdul Aziz, Amirudin (Universiti Putra Malaysia Press, 2019)
Majority of city dwellers do not engage in regular physical activities due to their built environments that are designed to favour travel by motor vehicles. Data from the Ministry of Health, Malaysia revealed 73% of the total deaths recorded were due to Non-Communicable Diseases (NCDs), of which, approximately 35% included Malaysians belonging to the working population (< 60 years). The first objective of this study was to investigate the physical inactivity among office workers through their perceived thermal hindrances on exposure to transient thermal conditions at three different building sites in Putrajaya. The second objective was to assess the awareness level of respondents regarding their physically inactive lifestyles. Respondents suffering from NCD were identified and their level of awareness in pursuing an active lifestyle was assessed. Perceived thermal hindrances that led to physical inactivity were measured by asking participants to rate their thermal sensation and thermal comfort votes at three different times of the working weekdays, namely, commuting from home to work (morning), lunch break (afternoon), and commuting from work to home (late afternoon). The results suggested that around 85% of respondents in Putrajaya were vehicle dependant that is they used private cars and motorbikes to and from work. Most of the respondents were willing to improve their health by walking more but expressed that the midday heat and natural humidity of the tropical weather coupled with the lack of shaded paths were partially reasons for them to opt for motor vehicles as their mode of transportation in Putrajaya.